Patients’ case scenario as well as approaches and strategies adopted to manage COVID-19 pandemic at Aligarh Muslim University, Aligarh, India (Bangladesh Journal of Medical Science, 2020)
Corona virus Disease 2019 (COVID-19) is a severe acute respiratory infection caused by corona virus-2 (SARS-CoV-2). It originated from Wuhan city of China in December 2019 and spread like a wild fire to the entire globe and was declared as global pandemic by WHO on March 11, 2020. With no available cure and vaccine, this disease has taken a mammoth toll on the human life; therefore, SMS (‘Social Distancing’, use of ‘Mask’ and regular hand washing with ‘Soap’) has emerged as a sole tool to prevent its spread. The Indian government declared the first lockdown from March 25th 2020 with subsequent second, third and fourth lockdowns up to 31st March 2020 to decrease the disease transmission and flatten the disease transmission curve. Aligarh Muslim University is one of the prestigious central and residential universities in India. It is located in Aligarh district adjoining national capital region. The university has an attached tertiary care ‘Jawaharlal Nehru Medical College Hospital’. This narrative review discusses the various steps and procedures taken up by the university and hospital administration, other functionaries, faculty members and doctors in tackling the serious pandemic until 22nd June 2020. The proactive role of administration, dedication and hard work of health care professionals and innovation of some academicians has given a new vista of opportunities to tackle this global health pandemic. The recovery rate of coronavirus patients at AMU hospital is recorded as 71.9%, which is much higher than national average recovery rate (56%). Thus, AMU model gives some positive insights to fight the current global pandemic.Bangladesh Journal of Medical Science Vol.19(0) 2020 p. S 28-S 35